2016
DOI: 10.18805/ijar.v0i0f.3789
|View full text |Cite
|
Sign up to set email alerts
|

Immunodiagnostic potency of homologous antigens for natural Haemonchus contortus infection in small ruminants in plate and paperenzyme linked immunosorbent assay

Abstract: The objective of this study was to characterize Haemonchus contortus antigens, and to standardize and evaluate indirect plate and dot-ELISA using homologous antigens in the small ruminants. Electrophoretic separation of somatic antigen in reducing condition on 15% polyacrylamide gel resolved into 16 proteins of molecular weight ranging from 14-100 kDa. Two step ethanolic extraction of the supernatant of in-vitro culture of H. contortus yielded excretory-secretory (E-S) antigen/ cathepsin L cysteine proteinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It was recently reported that concentration on the development of potential diagnostic tests was not only limited to H. contortus detection, but also on the development of new molecular vaccines and anthelmintic chemicals against Haemonchosis [6,20]. The antigen preparations used in diagnostic assays were primarily derived from whole worm extract, excretory and secretory worm products, sonicated egg antigens, partially purified fractions, and recombinant antigens [21]. The crude somatic antigen was evaluated for the immunodiagnosis of H. contortus infection [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently reported that concentration on the development of potential diagnostic tests was not only limited to H. contortus detection, but also on the development of new molecular vaccines and anthelmintic chemicals against Haemonchosis [6,20]. The antigen preparations used in diagnostic assays were primarily derived from whole worm extract, excretory and secretory worm products, sonicated egg antigens, partially purified fractions, and recombinant antigens [21]. The crude somatic antigen was evaluated for the immunodiagnosis of H. contortus infection [22].…”
Section: Discussionmentioning
confidence: 99%
“…Five crossbred goats were experimentally infected with 8000 H. contortus L3. Serum samples were collected from each goat before infection (negative control) and at 7,14,21,35,49,63,85, and 103 DPI.…”
Section: Serum Samplementioning
confidence: 99%
“…are prevalent in goats of northeastern region. Among the various GI nemotodes, H. contortus is the most prevalent and highly pathogenic parasite in small ruminants causing fatal anaemia (Das et al, 2018). Efficacy of synthetic anthelmintic drugs has been reduced due to its indiscriminate uses and lead to the development of anthelmintic resistance (AR).…”
Section: Introductionmentioning
confidence: 99%